2019
DOI: 10.1107/s2059798318017941
|View full text |Cite
|
Sign up to set email alerts
|

Journey to the center of the protein: allostery from multitemperature multiconformer X-ray crystallography

Abstract: Proteins inherently fluctuate between conformations to perform functions in the cell. For example, they sample product-binding, transition-state-stabilizing and product-release states during catalysis, and they integrate signals from remote regions of the structure for allosteric regulation. However, there is a lack of understanding of how these dynamic processes occur at the basic atomic level. This gap can be at least partially addressed by combining variable-temperature (instead of traditional cryogenic tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 137 publications
(159 reference statements)
1
32
0
Order By: Relevance
“…Variable temperature crystallography uses discrete temperature steps to sample the protein conformational landscape (Keedy, 2019). Given the experimental obstacles, there are only a few examples of ‘temperature titrations’ since the pioneering efforts mentioned above (Frauenfelder et al ., 1979; Tilton et al ., 1992).…”
Section: Looking Back and Moving Forward – Lessons Learnedmentioning
confidence: 99%
“…Variable temperature crystallography uses discrete temperature steps to sample the protein conformational landscape (Keedy, 2019). Given the experimental obstacles, there are only a few examples of ‘temperature titrations’ since the pioneering efforts mentioned above (Frauenfelder et al ., 1979; Tilton et al ., 1992).…”
Section: Looking Back and Moving Forward – Lessons Learnedmentioning
confidence: 99%
“…Testing these models and obtaining foundational information about active site positioning and conformational heterogeneity requires the conceptual perspective of the protein conformational energy landscape and resultant conformational ensembles, as introduced by Frauenfelder and coworkers (Austin et al, 1975;Frauenfelder et al, 1979Frauenfelder et al, , 1991 and as is now commonly invoked (e.g., Boehr et al, 2009;Fraser et al, 2011;Keedy, 2019;Smith et al, 1990;Wand et al, 2013). Testing these models also requires new experimental tools to obtain ensembles, which have been limiting until recently.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray damage and multitemperature X-ray crystallography. Cryo-cooling can alter conformational heterogeneity, and it has been found that over one-third of residues in protein crystals exhibit different and generally broader distribution of states at room temperture (15,18,23,30,78). Temperature-induced changes could be localized or could propagate throughout the protein, and our analysis of proteinase K provided an example of propagated temperatureinduced changes where freezing appears to hinder a long-range rotameric side-chain rearrangement by hindering the ability of water molecules to reorient when frozen.…”
Section: Discussionmentioning
confidence: 82%
“…In principle, the temperature dependence of a conformational ensemble can provide information about the forces underlying the energy landscape, and particular attention has been paid to changes arising from the so-called glass transition around 180-220 K (30,79,80). More broadly, an exciting new approach termed "Multitemperature Multiconformer X-ray crystallography" (MMX) was recently proposed in which a series of datasets obtained at various temperatures can be used to follow changes in rotameric distributions with temperature and could be exploited to uncover energetic coupling between states and provide testable hypothesis about allostery in proteins (30,78). Our results show that effects from X-ray damage can alter these conclusions.…”
Section: Discussionmentioning
confidence: 99%